2021
DOI: 10.1111/are.15153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow velocity on growth and physiology of juvenile largemouth bass ( Micropterus salmoides ) in recirculating aquaculture systems

Abstract: The cultivation of largemouth bass (Micropterus salmoides) in recirculating aquaculture systems (RAS) has become a growing trend. To ensure the welfare of juvenile largemouth bass in RAS, the effects of different flow velocities on their growth and physiology were explored, considering the flow velocity in real production. Following the stable water quality, juvenile largemouth bass with a body mass of 1.92 ± 0.38 g and body length of 4.50 ± 0.36 cm were reared at three different flow velocities of high flow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Shi et al 232 demonstrated that sustained swimming training have direct effects on filet texture of European seabass. Moreover, different flow velocities had significant effects on the growth, digestive enzyme activities, antioxidant capabilities, and immune capabilities of juvenile largemouth bass ( Micropterus salmoides ) in recirculating systems (RAS) 233 . A study on Nile tilapia showed that water flow can help the fish to cope better with stressful events, such as being introduced into novel environments 234 .…”
Section: Environmental Enrichment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al 232 demonstrated that sustained swimming training have direct effects on filet texture of European seabass. Moreover, different flow velocities had significant effects on the growth, digestive enzyme activities, antioxidant capabilities, and immune capabilities of juvenile largemouth bass ( Micropterus salmoides ) in recirculating systems (RAS) 233 . A study on Nile tilapia showed that water flow can help the fish to cope better with stressful events, such as being introduced into novel environments 234 .…”
Section: Environmental Enrichment Strategiesmentioning
confidence: 99%
“…Moreover, different flow velocities had significant effects on the growth, digestive enzyme activities, antioxidant capabilities, and immune capabilities of juvenile largemouth bass (Micropterus salmoides) in recirculating systems (RAS). 233 A study on Nile tilapia showed that water flow can help the fish to cope better with stressful events, such as being introduced into novel environments. 234 In addition, optimal exercise may also have beneficial effects on reproduction control.…”
Section: Hydrodynamism: Flow Currents and Exercisementioning
confidence: 99%
“…In this experiment, the total volume of water in the RAS was 110 L and a 25 L reservoir was used instead of a biofilter. Theory predicted maximum ammonia concentration was about 3.6 mg/L, which was in the safe range [24] .…”
Section: Ammonia Excretion Pattern Experimentsmentioning
confidence: 94%
“…Kvamme et al [34] found that the ammonia discharge rate of Atlantic salmon decreased with an increasing flow rate in the range of 0.2-0.5 L/(kg•min). Chen et al [24] found that the digestive enzyme activity of juvenile largemouth bass was enhanced as the flow velocity increased, which may also lead to enhanced protein uptake and reduced ammonia nitrogen excretion. To date, there is no general consensus as to the effects of flow velocity on the swimming and metabolism of fish species.…”
Section: Table 3 Coefficients Of Ammonia Excretion Model At Different...mentioning
confidence: 99%
“…Furthermore, a higher water velocity can make more particles suspend in the water, which is conducive to the filtration and removal of suspended particles. So, increasing the water velocity in the peak of ammonia discharge can contribute to the ammonia degradation and water purification (Chen, 2021). Therefore, it is beneficial to provide an appropriate water flow rate for the species cultured.…”
Section: Water Velocity and Exchange Ratementioning
confidence: 99%